Molecular Identification of Brown Algae Sargassum sp. from the Lombok Coastal Waters - Agus Sabdono; Yeni Sulistiyani; Norma Afiati; Haeruddin Haeruddin (Universitas Diponegoro, 2022)
Sargassum is a well-known genus of brown algae in Indonesia that has long been investigated due to its economic importance. To support its biological research, it is important to identify and classify the species studied. Morphological identification had greatly contributed to taxonomy, however, it cannot distinguish Sargassum species accurately due to its plasticity. The current study aims to identify Lombok Sargassum molecularly using an ITS2 DNA barcode. Fresh algae were collected from Ekas Bay (EB) and Aan Cape (AC) in Lombok. DNA was first purified, and then its gene product was amplified using ITS2 primers. DNA sequences were examined and traced using the Basic Local Alignment Search Tool (BLAST). DNA sequences were processed in MEGA-X to reconstruct the phylogenetic tree and estimate the genetic distance. Three species were identified based on the BLAST results: Sargassum cf granuliferum, Sargassum polycystum, and Sargassum oligocystum. The base length obtained ranged from 521 to 637 bp, with a similarity percentage of 99.25 to 100%. The phylogenetic tree exhibited each recognized Sargassum species was clustered with the same species from the gene bank. Interspecies genetic distance was 0,000-0,0039, while amongst Sargassum species it's 0,0136-0,2395. The genetic distance between Sargassum and Ulva adherens (outgroup) was >1. Sargassum species found in Lombok were closely related to other similar species in the GenBank.